2013
DOI: 10.1128/aac.01017-13
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus fumigatus Hyphal Damage Caused by Noninvasive Radiofrequency Field-Induced Hyperthermia

Abstract: We studied the effect of noninvasive radiofrequency-induced hyperthermia on the viability of Aspergillus fumigatus hyphae in vitro. Radiofrequency-induced hyperthermia resulted in significant (>70%, P < 0.0001) hyphal damage in a time and thermal dose-dependent fashion as assessed by XTT [(sodium 2,3,-bis(2-methoxy-4-nitro-5-sulfophenyl)-5-[(phenylamino)-carbonyl] (1)-2H-tetrazolium inner salt)], DiBAC [bis-(1,3-dibutylbarbituric acid) trimethine oxonol] staining, and transmission electron microscopy. For comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…It is reported that cumulative equivalent minutes (CEM 43 ), the metric of thermal tissue damage at 43 C, CEM 43 ¼ 2.7 min can damage cornea when hyperthermia achieved by ultrasound, whereas diode laser heating did not show any damage in the cornea at CEM 43 up to 1.26 Ã 10 3 min [3]. Kaluorachi et al have demonstrated Aspergillus fumigatus hyphal damage caused by noninvasive radiofrequency field induced hyperthermia (RFHT) [16]. RFHT exposure resulted in damage of 70% of the hyphae over 5 min and a 10 min exposure to RFHT at 48.09 caused extreme hyphal damage (>90%).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that cumulative equivalent minutes (CEM 43 ), the metric of thermal tissue damage at 43 C, CEM 43 ¼ 2.7 min can damage cornea when hyperthermia achieved by ultrasound, whereas diode laser heating did not show any damage in the cornea at CEM 43 up to 1.26 Ã 10 3 min [3]. Kaluorachi et al have demonstrated Aspergillus fumigatus hyphal damage caused by noninvasive radiofrequency field induced hyperthermia (RFHT) [16]. RFHT exposure resulted in damage of 70% of the hyphae over 5 min and a 10 min exposure to RFHT at 48.09 caused extreme hyphal damage (>90%).…”
Section: Introductionmentioning
confidence: 99%